E-Commerce Across European Union - Paula-Elena Diacon; Andreea-Nicoleta Donici (CES Working Papers, 2011)
In the last decade, the internet has evolved in an amazing tool having a major impact on all life aspects. The possibility to make online transactions, without being necessary to leave the house, was something new, an idea which changed from that moment the way business were made and perceived. Sites like mazon.com and eBay were and still are pioneers in this industry. E-commerce, a term that used to be unknown, has became nowadays one of the most tremendous and exciting trends in all kind of businesses. As a matter of fact it is for sure an essential element which helps at the growing at a national level, in terms of trade. As a result, the small companies are helped to internationalize their business and give them the opportunity to new business perspectives. The European Union understood these changes from the beginning of this phenomenon, recognizing the importance of electronic e-commerce.
Keywords: L81; 330; electronic e-commerce; European Union; internet; technology; globalization Romania